2017
DOI: 10.1111/jpy.12515
|View full text |Cite
|
Sign up to set email alerts
|

Comparative DNA sequence analyses of Pyramimonas parkeae (Prasinophyceae) chloroplast genomes

Abstract: Prasinophytes form a paraphyletic assemblage of early diverging green algae, which have the potential to reveal the traits of the last common ancestor of the main two green lineages: (i) chlorophyte algae and (ii) streptophyte algae. Understanding the genetic composition of prasinophyte algae is fundamental to understanding the diversification and evolutionary processes that may have occurred in both green lineages. In this study, we sequenced the chloroplast genome of Pyramimonas parkeae NIES254 and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…). While such differences might suggest the possibility that the two investigated P. parkeae strains are different species, a phylogeny based on 18S rDNA, rbc L, and chloroplast 16S rDNA sequences indicated that the two strains together form a monophyletic group separate from other studied Pyramimonas strains (Satjarak and Graham ). Additional molecular data from other P. parkeae strains and Pyramimonas species would be useful for future examination of intraspecific variability in mitochondrial genomes and its relevance to evolutionary diversification patterns.…”
Section: Discussionmentioning
confidence: 89%
“…). While such differences might suggest the possibility that the two investigated P. parkeae strains are different species, a phylogeny based on 18S rDNA, rbc L, and chloroplast 16S rDNA sequences indicated that the two strains together form a monophyletic group separate from other studied Pyramimonas strains (Satjarak and Graham ). Additional molecular data from other P. parkeae strains and Pyramimonas species would be useful for future examination of intraspecific variability in mitochondrial genomes and its relevance to evolutionary diversification patterns.…”
Section: Discussionmentioning
confidence: 89%
“…Rates of nucleotide substitution were previously shown to be several times slower in the plastid IR regions compared with SC regions in other angiosperms, suggesting that IR regions provide enhanced copy-correction activity [49]. Gene conversion has been shown to be biased towards copy-dependent repair mechanisms [50]. This phenomenon is possibly due to error correction occurring via gene conversion between Irs [51].…”
Section: Resultsmentioning
confidence: 99%
“…The availability of algal and higher plant chloroplast genome sequences has enhanced the understanding of their evolutionary relationships by strengthening the reliability of taxonomic classification [ 29 ] and facilitating reassessment of previous species classifications [ 30 ] to reveal new insights into global genomic and evolutionary relationships. Recent genome analyses have revealed subspecies divergence among C. sorokiniana variants [ 31 ], also contributing to a better understanding of gene composition, as well as photosynthetic and metabolic pathways conducive to genetic modification [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%